Inhibition by SEA0400, a Selective Inhibitor of Na+/Ca2+ Exchanger, of Na+-Dependent Ca2+ Uptake and Catecholamine Release in Bovine Adrenal Chromaffin Cells - Shin Soma; Haruhiro Kuwashima; Chiaki Matsumura; Tomohiko Kimura (Elsevier, 2006)
The effects of SEA0400, a selective inhibitor of the Na+/Ca2+ exchanger (NCX), on Na+-dependent Ca2+ uptake and catecholamine (CA) release were examined in bovine adrenal chromaffin cells that were loaded with Na+ by treatment with ouabain and veratridine. SEA0400 inhibited Na+-dependent 45Ca2+ uptake and CA release, with the IC50 values of 40 and 100 nM, respectively. The IC50 values of another NCX inhibitor KB-R7943 were 1.8 and 3.7 µM, respectively. These results indicate that SEA0400 is about 40 times more potent than KB-R7943 in inhibiting NCX working in the reverse mode. In intact cells, SEA0400 and KB-R7943 inhibited CA release induced by acetylcholine and DMPP. The IC50 values of SEA0400 were 5.1 and 4.5 µM and the values of KB-R7943 were 2.6 and 2.1 µM against the release induced by acetylcholine and DMPP, respectively, indicating that the potency of SEA0400 is about a half of that of KB-R7943 in inhibiting the nicotinic receptor-mediated CA release. The binding of [3H]nicotine with nicotinic receptors was inhibited by SEA0400 (IC50 = 90 µM) and KB-R7943 (IC50 = 12 µM). From these results, it is concluded that unlike KB-R7943, SEA0400 has a potent and selective action on NCX in bovine adrenal chromaffin cells. Keywords:: SEA0400, Na+/Ca2+ exchanger, Ca2+ uptake, catecholamine release, adrenal chromaffin cell